EVALUATION MODEL FOR INDONESIAN LANGUAGE LEARNING AT MTS MIFTAHUL KHOIR - Febriansyah, Ahmad; Syamsiyah, Nur (Jurnal Evaluasi dan Pembelajaran, 2024)
This study explains the model of learning development and evaluation in Indonesian subjects at MTs Miftahul Khoir. The main objective of this study is to explore the learning development and evaluation model as an effort to improve the quality of students in understanding Indonesian lessons. This study used a qualitative descriptive approach. Data collection methods involve interviews, observation, and documentation. Data analysis is carried out through three stages: reduction, presentation of data, and drawing conclusions. The results showed that 1) the Indonesian learning development model in MTs Miftahul Khoir involves reading, listening/listening, writing, and dialogue/speaking models, 2) Evaluation of the learning model is carried out with daily tests, midterm tests, quick quizzes, and through the results of discussions and questions and answers to students. The headmaster engages in class visits and reports on learning outcomes at the end of the semester as part of the learning evaluation, in an effort to improve students' abilities and achievements in Indonesian.